Bioactivity-Guided Isolation of Neuritogenic Factor from the Seeds of the Gac Plant (Momordica cochinchinensis) - Mazzio, E. (Evid Based Complement Alternat Med, 2018)
Nerve growth factor (NGF) is an endogenously produced protein with the capacity to induce central nervous system (CNS) neuronal differentiation and repair. NGF signaling involves its binding to tropomyosin-related kinase (Trk) receptors, internalization, and initiation of phosphorylation cascades which cause microtubule reorganization and neuronal outgrowth. Because NGF cannot cross the blood-brain barrier, its therapeutic use is limited. Synthetic peptides that can act as NGF receptor agonists (NGF mimetics) are known to attenuate neurodegenerative pathologies in experimental models of Alzheimer's disease and Parkinson's disease; however, the existence of plant-based NGF mimetics is uncertain. For this reason, we recently completed a high throughput screening of over 1100 nutraceuticals (vitamins, herbal plant parts, polyphenolics, teas, fruits, and vegetables) to identify neuritogenic factor using a PC-12 cell model. Remarkably we found only one, commonly known as the seed of Gac plant (Momordica cochinchinensis) (MCS). In the current study, we further investigated this seed for its neuritogenic effect using bioactivity-guided chemical separations. The data show no biological neuritogenic activity in any chemical solvent fraction, where activity was exclusive to the crude protein. MSC crude proteins were then separated by 1D electrophoresis, where the active neuritogenic activity was confirmed to have a molecular mass of approximately 17 kDa. Subsequently, the 17kDa band was excised, digested, and run on a UPLC-MS/MS with a Q Exactive Hybrid Quadrupole-Orbitrap Mass Spectrometer with data evaluated diverse tools such as X! Tandem, OMS, and K-score algorithms. Proteomic evaluation of the 17kDa band confirmed evidence for 11S globulin subunit beta, napin, oleosin, Momordica trypsin inhibitors (TI) MCoTI-I /II, and many isoforms of Two Inhibitor Peptide Topologies (TIPTOPs). While all peptides identified correspond to the genus/species, Momordica cochinchinensis and Cucumis Sativus, a significant limitation of the analysis is the nonexistence of full annotation for the Momordica cochinchinensis proteome. In conclusion, these findings demonstrate that there is a stable protein within MCS having a mass of 17kDa with the capacity to induce neurite outgrowth. Future work will be required to establish the therapeutic value of the MCS for the treatment of neurodegenerative diseases.